Land degradation associated with coal mining in Salanpur block, Paschim Bardhaman district, West Bengal - Sangita Mahata; Vishwambhar Nath Sharma (National Geographical Journal of India, 2023)
Mining activities in Salanpur block of Paschim Bardhaman district of West Bengal has created an acute threat to the soil quality of surrounding agriculture fields, which in turn has affected the soil ecosystem in the long run. No matter how binding environmental laws, plans, and policies are, a well-informed society is more likely to conserve the land than an ignorant one. Large amount of fertile land are wiped out every year due to opencast coal mining. Harmful toxic metals settled down in agricultural field and abandoned areas. Thus, people residing in and around the mining areas often complain about low yield productivity of crops and decline in soil fertility of the surrounding land. The paper attempts to find out the causes of land degradation in Salanpur block as a result of declining soil quality due to open cast mine. The samples were analyzed for PH, total nitrogen (N), extractable zinc (Zn), extractable manganese (Mn), and extractable iron (Fe). Deficits of micronutrients in soils are usually assessed for the need to fertilize it with micronutrients, while, deficiencies develop below the optimum concentration, and toxicity develops above. The samples from the coal mine affected areas shows soil quality deficit condition. The increasing productivity of agriculture has soared the demand for secondary and micro nutrients in soil fertility management as a result of intensification of agriculture.